PERANCANGAN ALAT BANTU UNTUK REMOVE AND INSTALL PISTON STEERING CYLINDER PADA UNIT HD1500-7 - Hendro Purwono; Rasma Rasma (University of Muhammadiyah Jakarta, 2018)
The number of jobs and the duration of the process of replacing the steering cylinder seals (reseal) on the HD1500-7 unit, especially when removing and installing the piston steering cylinder on the rod by a mechanic causes the loss of rental costs and failure to achieve the company's target due to breakdown. The purpose of this study is to design tools to shorten the time and simplify the process in order to minimize the loss of rental costs and more secure. The method used in this research is field survey, interview, and library research. The results obtained after the new tool indicate a time efficiency of 1 hour for one-time processing and can reduce the loss of rental costs of 70 (Rp.910.000) and safer for demage and mechanical properties because of the potential slip when the tool is used.